Injuries in Physically Disabled Children - Kraus, Tanja; Singer, Georg; Wegmann, Helmut; Tschauner, Sebastian; Svehlik, Martin; Steinwender, Gerhard; Sorantin, Erich (Seminars in Musculoskeletal Radiology, 2014)
Disability is a condition or function that is judged to be significantly impairing relative to the usual standard of an individual or group. The spectrum of musculoskeletal disabilities in children is immense and varied. Musculoskeletal disabilities are congenital or acquired; they affect a child partially or generally and can occur as a permanent or transient disability.Although injuries still represent a major concern for children and adolescents worldwide, studies focusing on injuries in physically disabled children are lacking. To detect musculoskeletal injuries, radiographs are frequently required. In disabled children the radiographic findings can detect the skeletal injury but also can present special radiographic findings of the underlying disease.This review offers an overview of different musculoskeletal disabilities and their related injuries as well as characteristic findings on radiographs.
Keywords: growing skeleton; disabled; osteoporosis; metabolism; injury